Addition and subtraction of fractions. - Harper & Row, Publishers (White Plains, N.Y. : Center for Humanities, 1979)
Topics covered include addition and subtraction of fractions with like denominators, of fractions with unlike denominators, and addition and subtraction of mixed numbers.
"The skills group."
Also issued with sound accompaniment on disc.
Keywords: Fractions; Addition; Subtraction